The Linguistic Worldview - Łozowski, Przemysław (De Gruyter, 2013)
The book is concerned with the linguistic worldview broadly understood, but it focuses on one particular variant of the idea, its sources, extensions, its critical assessment, and inspirations for related research. This approach is the ethnolinguistic linguistic worldview (LWV) program pursued in Lublin, Poland, and initiated and headed by Jerzy Bartmiński. In its basic design, the volume emerged from the theme of the conference held in Lublin in October 2011: "The linguistic worldview or linguistic views of worlds?" If the latter is the case, then what worlds? Is it a case of one language/one worldview? Are there literary or poetic worldviews? Are there auctorial worldviews? Many of the chapters are based on presentations from that conference, and others have been written especially for the volume. Generally, there are four kinds of contributions: (i) a presentation and exemplification of the "Lublin style" LWV approach; (ii) studies inspired by this approach but not following it in detail; (iii) independent but related and compatible research; and (iv) a critical reappraisal of some specific ideas proposed by Jerzy Bartmiński and his collaborators.